Consumer Boycotts and Their Impact on the Relationship Between Brand Awareness and Purchase Intentions - Achbar Adi Saputra; Dwi Nita Aryani; Azura Abdullah Effendi; Virly Assa Lunsa; Xu Congbo; Chew Kah Song; Syed Noor Izhar (International Journal of Tourism and Hospitality in Asia Pasific, 2025)
The global boycott movement against pro-Zionist products has intensified as an act of solidarity, leading to a notable decline in the sales and market value of companies associated with Zionism. This research analyzed the effect of brand awareness on consumer purchase intention, with pro-Zionist product affiliation as a moderating variable. The study involved 110 respondents from Indonesia (52), Malaysia (33), and China (25). The results revealed that brand awareness had a significant positive influence on consumer purchase intention (t = 5.770; Sig. = 0.000), indicating that higher brand recognition and recall strengthen consumers’ willingness to buy. However, the moderating effect of pro-Zionist product affiliation showed a significant negative coefficient (B = -0.100; t = -4.820; Sig. = 0.000), demonstrating that boycott awareness weakens the relationship between brand awareness and purchase intention. This suggests that even when consumers are familiar with a brand, their intention to purchase declines if the brand is perceived to support Zionism. Overall, the findings confirm that while brand awareness remains a dominant factor in shaping consumer purchase decisions, political associations such as pro-Zionist affiliations can significantly reduce consumers’ willingness to buy. These results emphasize the importance of corporate neutrality and value alignment in maintaining consumer trust and loyalty.